Odpowiedzi

2010-04-07T15:21:04+02:00
A) 3x+15=-2x-5
3x+2x=-5-15
5x=-20/5
x=-4
b)2(x-5)=0,5x+5
2x-10=0,5x+5
2x-0,5x=5+10
1,5x=15/1,5
x=10
c)-x+12=-2(x+1)
-x+12=-2x-2
-x+2x=-2-12
x=-14
d)-1\3(ułamek)x+5=2/3(ułamek)x-4 /*3
-x+15=2x-12
-x-2x=-12-15
-3x=-27/-3
x=9
2010-04-07T15:38:48+02:00
A)
3x+15=-2x-5
3x+2x=-5-15
5x=-20/5
x=-4

b)
2(x-5)=0,5x+5
2x-10=0,5x+5
2x-0,5x=5+10
1,5x=15/:1,5
x=10

c)
-x+12=-2(x+1)
-x+12=-2x-2
-x+2x=-2-12
x=-14

d)
-1\3x+5=2/3x-4 /*3
-x+15=2x-12
-x-2x=-12-15
-3x=-27/-3
x=9